Towards the development of sustainable control options for the African root and tuber scale on cassava in Central Africa understanding the ecology of the associated ant Anoplolepis tenella - Fotso Kuate, A.; Hanna, R.; Tindo, M.; Nage, P. (International Society for Tropical Root Crops, 2012)
Anoplolepis tenella Santschi is an afrotropical ant widely distributed in the forest zones of Central Africa. It is the most frequent species associated with the African root and tuber scale (ARTS) Stictococcus vayssierei (Hemiptera: Stictococcidae), an afrotropical insect that infests a wide range of root and tuber plants, particularly cassava. We investigated the biology and ecology of A. tenella which is one of the factors favoring the proliferation of the scale in the field. A. tenella was more abundant in the mixed-crop fields. It was rare or absent in the lowland where the scale was also absent. A. tenella is actively engaged in the transport and dispersal of scale crawlers. Boric acid-sucrose solution significantly killed A. tenella workers and queens under laboratory conditions. This result was later demonstrated in a farmer participatory trial and reduced scale infestation on cassava. These results demonstrate that control of S. vayssierei in cassava fields is contingent to the reduction of the density of the associated ant A. tenella.